PERANCANGAN BUKU OBJEK WISATA KOTA PADANG - Ria Sofiana, Drs. Ariusmedi, M.Sn, Ishakawi, S.Pd, M.Ds (DEKAVE : Jurnal Desain Komunikasi Visual, 2013)
Purpose of this final work is (1) Design books as media campaigns and information for the community or outside the of Padang city, which discusses the attractions in the of Padang city (2) Designing an interesting book, specify color, typography, layout communicative to the public so that it has its own characteristics. Sources of this final work is the method of data collection in the form of field observations, interviews, as well as through the documentation on the attractions in the of Padang city. Final work in the form of a book in which there is communicative to the public information about the attraction of Padang with explanations and images, color, typography, and layout are interesting. Keyword: design, book, attraction, Padang city.